(untitled) (Journal of Dhaka Medical College, 2025)
Background: Early prediction of GDM by measuring a biomarker at first trimester of pregnancy may prevent maternal and fetal complication. Adiponectin, which modulate insulin sensitivity, is secreted from adipose tissue and decreases blood glucose level. The objective of the study was to evaluate the association of maternal first trimester serum adiponectin with development of GDM. Methodology: This longitudinal study was conducted in the BSMMU, Dhaka from June, 2021 to May, 2022 where pregnant women of first trimester were selected by purposive convenient sampling. At first 94 pregnant women were selected after excluding diabetes or previous history of GDM and their serum adiponectin level was measured. Then the participants were followed up at 24-28 weeks of gestation and OGTT was done to detect GDM. ROC was used to decide the best cut-off point of adiponectin level for detection of GDM. The respondents were divided into ‘below cut-off’ group and ‘above cut-off’ group. Differences between two groups were assessed by statistical test. Results: A total 18 respondents developed GDM from both group. In below cut-off’ group, out of 26 respondents 13 developed GDM and remaining 13 were euglycemic. Whereas in above cut-off group, out of 62 respondents, majority 57 were euglycemic and only 5 women developed GDM. ROC analysis of adiponectin level for detection of GDM, a AUC value 0.887 (95% confidence interval 0.802-0.972) was found which was statistically significant (p<0.001). A cut off value of <s10.165 mg/ml showed the highest youden index (0.651) with 83.3% sensitivity and 81.4% specificity, the accuracy was 79.5%. Moreover a cut of value <s10.165 mg/ml showed PPV and NPV of 50.8% and 92.8% respectively. A significant association was found between development of GDM and adiponectin level (P<0.001). The odds for developing GDM due to low adiponectin are 11.4 [95% CI: 3.45 – 37.64]. About 72.2% GDM patients had below cut-off adiponectin level. Conclusion: Study finding revealed that maternal serum adiponectin level was lower at early pregnancy to those patients who subsequently developed GDM. So a low adiponectin level at early pregnancy may be a new risk factor for GDM. J Dhaka Med Coll. 2024; 33(1) : 27-31